Euro pean Islamic relations (Journal of the College of Basic Education, 2023)
The issue of relations in all its aspects, whether Political or Commercial, aswellqs Cultural, is considered one of the important topics in the history of relations between East and west, asit had its own character in every Stage of the history of the Arad- IsLamic State, especially since it extended for aLovg period of time and took wany different forms Circumstances and events.